Canva- Based Interactive Media to Increase Students ' Interest in Learning Class V State Primary School 19 Dulupi (Global Scientific Review, 2023)
This Canva-based interactive media development research aims to increase elementary school students' interest in learning. The research method used is Research and Development (R&D) and uses a 4-D development model which consists of four stages, namely 1) Define 2) Design 3) Develop 4) Disseminate. Product validation is carried out by experts with an expert validation sheet. The practicality of the product was tested on teachers and the effectiveness was tested on students in small groups of 5 students as well as large field trials on 13 students and continued by distributing questionnaires with the aim of seeing students' responses to the media. The research used questionnaires, interviews and documentation as data collection instruments.